Curvature-Dependent Reflectance Function for Interactive Rendering of Subsurface Scattering - Kubo, Hiroyuki; Dobashi, Yoshinori; Morishima, Shigeo (International Journal of Virtual Reality, 2011)
Simulating sub-surface scattering is one of the most effective ways to realistically synthesize translucent materials such as marble, milk or human skin. We have developed a curvature-dependent reflectance function (CDRF) which mimics the presence of subsurface scattering. In this approach, we provide only a single parameter that represents the intensity of theincident light scattered in a translucent material. The parameter is not only provided by curve-fitting to a simulated data-set, but also manipulated by an artist. Furthermore, this approach is easily implementable on a GPU and does not require any complicated pre-processing and multi-pass rendering as is often the case in this area of research.